Paper-based flexible electronic devices: processing, integration, and applications - Wenfeng Ying; Chuanyu Zhou; Huibin Sun; Wei Huang (npj Flexible Electronics)
Abstract This paper provides a comprehensive review of the research progress in paper-based flexible electronic devices, focusing on key aspects such as the physical and chemical properties of paper substrates, device structures, fabrication methods for electrodes and active layers, and their diverse applications. The paper also identifies current challenges facing paper-based electronic devices, such as issues related to long-term stability and the optimization of large-scale production processes.